Reputation management and family business - Zdzisława Dacko-Pikiewicz (Routledge, 2022)
"Corporate reputation is important in gaining long-term competitive advantage and building company value. Thus, the author points out the need to manage reputation, which, due to its complex nature and multidimensional character, is a serious and difficult challenge. The author develops a strategic model for family business reputation management. The book presents the review, systematization and synthesis of views on the notion of reputation and its role in building company value, the determinants of reputation; the identification of the characteristics and distinguishing factors of family businesses, areas of reputation building and resources involved in family business reputation building processes; and the description of determinants, components and processes in the field of corporate reputation management, and the identification of key links between them. It also identifies the key elements of the concept of family business reputation management and the relationship between them and practical recommendations for the use of reputation management concepts in improving the functioning of family businesses. The developed model can undoubtedly be seen as a pioneering contribution to research into the competitiveness of enterprises. The book will therefore be useful to researchers, students and managers who are interested in decision-making in family businesses, entrepreneurship and small business management, and leadership studies"–
Keywords: 330; Management and management techniques; Management: leadership and motivation; Business strategy; Entrepreneurship; Familienunternehmen; Firmenimage